2021
DOI: 10.1111/mcn.13162
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothers: Central scaffolding sources impacting maternal and infant feeding practices in Colombia

Abstract: A growing body of evidence highlights that maternal and child nutrition programmes need to extend beyond the mother–child dyad by adopting a family systems approach, particularly in the Global South. Guided by a sociocultural and community psychology understanding of health, the paper explores factors identifying grandmothers as central resources for nutrition programmes. The study was conducted in a Colombian urban periphery applying a qualitative longitudinal design (prenatal and postpartum). It is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
3
3
0
Order By: Relevance
“…This is consistent with a growing body of work showing the importance of grandmothers(Concha & Jovchelovitch, 2021), other women(Usman et al, 2021) and spouses(Morrison et al, 2021) in shaping maternal and child nutrition-related behaviours, and in increasing the impact of behaviour change interventions (Narayanan…”
supporting
confidence: 87%
See 1 more Smart Citation
“…This is consistent with a growing body of work showing the importance of grandmothers(Concha & Jovchelovitch, 2021), other women(Usman et al, 2021) and spouses(Morrison et al, 2021) in shaping maternal and child nutrition-related behaviours, and in increasing the impact of behaviour change interventions (Narayanan…”
supporting
confidence: 87%
“…Cooperation may occur in several ways, for example, by sharing risk and information, sharing tasks and gains from agricultural production and sharing the responsibilities of raising children. Some studies have highlighted men's role in supporting their wife's access to antenatal and post‐natal care (Barua et al, 2004 ; Morrison et al, 2021 ), and their children's access to an adequate diet (Han et al, 2019 ; Nyqvist & Jayachandran, 2017 ), while a growing literature has highlighted the role of grandmothers in improving nutrition outcomes (Aubel, 2012 ; Concha & Jovchelovitch, 2021 ; Negin et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…This high grandmaternal involvement in primary care reflects traditional values of familismo (Sotomayor‐Peterson et al., 2012) and stands in contrast to the rather fun‐providing grandmother role observed in Western contexts (Sandel et al., 2006; Sticker, 1991). Furthermore, whereas a study conducted in Los Angeles, US, and Berlin, Germany, revealed that grandmothers adapt their ethnotheories to their children's opinions (Keller and Demuth, 2006), grandmothers are considered important sources of advice in our sample, consistent with research in other non‐Western contexts (e.g., Concha and Jovchelovitch, 2021; Kerr et al., 2008). These differences to urban WEIRD contexts clearly show that urban Western and urban non‐Western families are distinct cultural contexts with different developmental conditions and that the study of different contexts is essential in examining universal assumptions about child development.…”
Section: Role Of Nonmaternal Caregivers Involved In Feedingsupporting
confidence: 86%
“…A 2021 special issue in Maternal & Child Nutrition compiled 11 articles that contribute evidence supporting the application of family systems framework to inform nutrition programs [ 21 ]. Several studies identify grandmothers as key influencers of health knowledge within the household and conclude that child nutrition interventions might benefit by intentionally including them [ 21 25 ]. For instance, Pike et al found that pregnant adolescents in Bangladesh reported feeling overwhelmed and inadequate to make decisions for themselves as young, first time mothers.…”
Section: Introductionmentioning
confidence: 99%